ANALYSIS OF THE HUMAN DEVELOPMENT INDEX BASED ON THE IMPLEMENTATION OF A PULP MILL IN MATO GROSSO DO SUL - Pacheco, Patricia Soares; Siroma, Priscila Aiko Hiane (Seven Editora, 2025)
The state of Mato Grosso do Sul stands out in the pulp and paper sector. This article analyzes the impact of the pulp industry on the Human Development Index (HDI) in a small municipality in Mato Grosso do Sul. To this end, a systematic review was conducted following the criteria of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Of the 178 articles found, 11 articles were selected that showed that to maximize benefits and mitigate risks, there must be integrated planning, with the participation of the community and local authorities, promoting development that respects human beings and the environment. Increasing income and education can increase the HDI, but environmental and social challenges must be managed effectively to ensure that development is sustainable. There is a need for sustainable practices, because if the industry compromises natural resources, it can have long-term impacts on health and the local economy, negatively affecting the HDI.DOI: https://doi.org/10.56238/sevened2025.029-057